Examining ISIS's Use of Terminological Amplification in its Media Publications - Abu-Melhim, Abdel-Rahman (International Journal of Language and Literary Studies, 2026)
The purpose of this study is to use textual interpretation to show that, in Dabiq Magazine, Issue 1, ISIS employed vocabulary to advance its belief system. The paper attempts to answer the question: What discursive strategies are utilized in Dabiq, paying special attention to how the group weaponized Islamic terminology to legitimize its violent ideology? The study systematically examines the nonexclusive Islamic terms ISIS regularly uses. ISIS advocates an adjustment to early Islamic social structures and advances brutal jihad philosophy. Accordingly, it argues that ISIS's utilization of non-specific Islamic terms methodologically fortifies jihad as the head of its methodology. It exhibits ISIS's inclination toward specific terms in its philosophy, thereby delineating its emphasis on certain branches of its belief system over others. The researcher applied Critical Discourse Analysis (CDA) as the primary research method. Based on discourse analysis of Dabiq Magazine, Issue 1, the results of the study revealed that ISIS props up brutal jihad as the main point of its methodology, which it embraced from Zarqawi. The study implied that in advancing its belief system, ISIS lays out specific rules for recruited people to put themselves in the thought of a reestablished period of Islamic human progress.